INTRODUCTION TO HORTICULTURE - KUMAR, N. (New Delhi Medtech, 2018)
The present enlarged edition covers four aspects in Horticulture viz., Fundamentals of Horticulture, Plant Propagation, Pomology and Ornamental Horticulture. It caters to the students of undergraduate programmes in Horticulture being offered in State Agricultural universities and Botany courses of the conventional universities.
Keywords: Botany; Plant; Horticulture